Heart rate monitoring - Treffene, B.
All the Australian swimming world record breakers since 1977 have used heart rate monitoring control in training control for the full season prior to their world record breaking performances. They had heart rate sets 2-3 times a week for leading up to national training camps and then continuously for the duration of the camps prior to major competitions. It has been found possible to use heart rate measurement to determine optimal training speeds for aerobic conditioning and also for suitable advice prior to competition for optimising performance in distance events. A standard 10 x 100m set introduced regularly into the program that is accurately timed and monitored coupled with monthly heart rate velocity data is used to determine adaptation phases that could then be used to control the following weeks program. This paper gives a brief description of the procedures used to determine training speeds, the adaptation phases, the types of sets and their frequency of use for optimal aerobic conditioning and where we are planning to head in the next decade. Each swimmer became aware of their maximum heart rate and were asked to swim so that their heart rate after the first 500 m is within 10 to 20 bpm of their maximum and after half the set within 10 bpm of their maximum. The maximum heart rate was revised if it was exceeded during these sets. These maximum heart rates were normally finally determined within the first three sessions. Contrary to expected not one of the swimmers have shown any different maximum heart rates despite being measured over periods up to eight years. A swimming coach interested in pre-race assessment of physical performance is often faced with the need to assess a person's circulatory performance fitness as it relates to performance potential. This has created the need for a simple test for such an evaluation based upon a submaximal work rate test. The simplest and most extensively applied way of testing the circulatory functional capacity is to determine heart rate during or after exercise (step test, treadmill or cycle ergometer test) and simultaneously measure the work load or oxygen uptake. From the heart rate work rate response the circulatory capacity can be evaluated (1, 2). By determination of Vcr within three days prior to competition advice was given on race pace. By comparison to previous Vcr values prior to competition the expected improvement in swimming time was able to be assessed and the swimmer was then advised of suitable early pace in their swims by the coach. During Training periods and sometimes in Taper the heart rate curves moved significantly and dramatically to the left. This indicated a loss in aerobic ability which has been found to recover gradually over about a ten day period. Training was maintained during this process but at reduced intensities so that the heart rate was still 10 to 20 bpm below their maximum heart rate. The gradual reduction in aerobic sets leading into the competition were designed to restrict these shifts to the periods three weeks out from competition. To improve Vcr it is therefore important to overload the factors that are important at critical speed namely high carbohydrate turnover and high oxygen uptake levels. The fat metabolism is not an important food substrate at Vcr speed. At critical speed the steady state blood lactate is higher than 4 m mol for most swimmers and therefore well above anaerobic threshold (22,25). When planning work routines it is important to decide that it is the overload of the oxygen uptake system which is important and not the overload of the fat metabolism. Most exercise tests are based on a linear increase in heart rate with increasing oxygen uptake or work load (2). The prediction of maximum oxygen intake from the response to submaximal efforts have been reported by Meritz et al (12) and also Shephard et al (14). Four paired observations of heart rate and work rate were made at increasing load, and a line fitted to the data was extrapolated to the individual's theoretical maximum heart rate. A critical speed (Vcr ) can be determined by extrapolation of the heart rate-velocity curve (17) to individual maximum heart rates or by extrapolation of oxygen uptake-velocity curves to individual maximum oxygen uptakes (8) by measurements taken immediately after controlled swims in a pool. Treffene (15, 17) and Treffene et al (20) have described a protocol using heart rates measured immediately after constant pace swims to calculate the minimal constant velocity, Vcr , at which a swimmer's heart rate achieves its maximum (Figure 1). The protocol used was similar to the recommended World Health Organisation multistage extrapolation method (1). However, the extrapolation of the heart rate-velocity curves of best fit were continued to the maximum heart rate which had previously been measured for each individual after intensive sets of 200m swims and not predicted heart rates. This intersection determined the critical velocity Vcr . Data using this test protocol has enabled detailed analysis of freestyle swimming events to be made (13, 19) which has subsequently been used in training control for Olympic swimmers. Heart rate control has been used on Australian elite freestyle swimmers for both distance swimmers and sprint swimmers (19). A major assumption in the physiological model used to explain the 200m freestyle performance results (19) was that the competition anaerobic capacity for the 100m, 200m, 400m and 1500m events was constant for each individual. Both the agreement of experimental results with predictions (19, 20) and the findings of Medbo et al (1988) that the accumulated oxygen deficit was constant for different maximal exercise time periods support the above assumption. Improvement in performance for competitors in freestyle is paralleled by an improvement in Vcr (18, 20). This enables one to anticipate improved times in competition relative to past recorded times by comparing corresponding hear rate-velocity curves. This has been used successfully to plan national, international and world record performances in freestyle events. The essential components of the protocol used for the conduction of the test to determine Vcr for each stroke are listed. (i) A normal competition pool of length 50 m was used for all swimming. (ii) The temperature of the pool water was maintained between 22· - 26· C which is normal for competition pool temperatures. (iii) The pool environment was controlled against the effect of winds. Pool pumps were switched off temporarily to avoid effects on swimming speeds. (iv) A multistage test involving 300 m swims at three or more constant speeds was used with short rests in between. (v) Heart rate measured immediately following swimming was assumed to be the same as the steady state heart rate immediately prior to finishing each 300m swim (15). (Note :- 200m is normally more convenient and will produce almost identical curves. If you use 200m then use it in all future tests for valid comparisons.) (vi) Both the swimmers and coaches involved were made fully aware of the pre-test and test requirements by suitable instructions being supplied. (vii) preliminary procedures on days before the test familiarised the subjects with the testing conditions. The coach is asked not to give any heavy working loads or high intensity efforts on the day preceding the tests and the swimmers should have experience with the testing procedure prior to the testing day. Prior to each test the swimmers particulars regarding height, weight, age, medical factors, and the time, date, pool temperature are recorded on a sheet used also for the swim recordings (Table 1). To control the swimming speeds of each subject, ideally walkers on the side of the pool should be used with predetermined lap time charts to control the speeds. These walkers will record each of the lap times for each swim (Table 1). The heart rate during each 200m will be assumed to plateau within the first two minutes of exercise. Useful data can also be obtained by only one person timing up to 6 swimmers who swim 20 seconds apart and assuming the swimmers maintain a constant speed over the last 100m of each 200m swim. The swimming speeds chosen will be between one sufficient to bring the subject's heart rate to 110 beats per minute for the slowest speed and a speed of approximately 80% of each swimmer's maximum speed for the final fastest speed. The swimmer, on finishing a 200m swim, presses the foam electrode to his chest. A beat by beat heart rate which is rapidly dropping is displayed. The highest heart rate in the smoothly dropping heart rates indicated is taken as the heart rate during work. (This beat should be detected within five seconds of the swimmer finishing or that reading should be discounted). The heart rate taken within five seconds of finishing each steady state swim will be taken as a measure of the heart rate during the last minute of the steady state swim. The maximum heart rate will be determined following a maximal 200m swim. Again this heart rate is measured within five seconds of finishing the swim. The 200m time should be within four seconds of that swimmer's recent best 200m time to be considered as a maximum effort. This maximum heart rate for each individual should be rechecked during maximal effort training. An indication that the heart rate represents a true maximum heart rate is also given by checking the point consisting of the average of the 200m speed (vmax) and the measured maximum heart rate (HRmax ) on the heart rate-velocity graph. (Vmax , HRmax ) should be a point displaced to the right of a reasonably smooth curvilinear relationship obtained from the submaximal speeds. If this is not the case the swimmer should be encouraged to repeat the 200m at a faster speed and the heart rate recorded.